2022
DOI: 10.1111/clr.13903
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of bone‐level assessments following reconstructive surgical treatment of experimental peri‐implantitis

Abstract: Aims The purpose of this study was to evaluate the accuracy of bone‐level assessments using either cone‐beam computed tomography (CBCT), intra‐oral peri‐apical (PA) radiographs or histology following reconstructive treatment of experimental peri‐implantitis. Materials and Methods Six Labrador dogs were used. Experimental peri‐implantitis was induced 3 months after implant placement. Surgical treatment of peri‐implantitis was performed and peri‐implant defects were allocated to one of four treatment categories;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Further, evaluations of MBL after the use of bone substitute materials are challenging and may have influenced the accuracy of radiographic assessments. Results from a preclinical in vivo study, however, indicated that the identification of marginal bone levels on conventional radiographic images is a reliable method, also after reconstructive therapy of peri‐implantitis (Almohandes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further, evaluations of MBL after the use of bone substitute materials are challenging and may have influenced the accuracy of radiographic assessments. Results from a preclinical in vivo study, however, indicated that the identification of marginal bone levels on conventional radiographic images is a reliable method, also after reconstructive therapy of peri‐implantitis (Almohandes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%